Adsorpsi Ion Logam Kromium (Cr (Vi)) Menggunakan Karbon Aktif dari Bahan Baku Kulit Salak - Selvya Utama; Hans Kristianto; Arenst Andreas (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Heavy metals are elements which are produced in industrial waste. This heavy metal waste causes pollution to the environment if the content of heavy metals contained therein exceeds the threshold. The toxic’s properties are extremely dangerous for humans if it accumulates in the human body. One of the heavy metals that are produced  is chromium. Several chemical and biological methods to remove heavy metals contained in the waste have been found. The adsorption method is one of the efficient and effective ways to treat heavy metal waste. In this study, activated carbon was prepared from salacca peel. Effects of pH, adsorbent dosage and Cr(VI) concentration on the adsorption of hexavalent chromium were investigated. The results were analyzed with Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich adsorption isotherm models. And kinetic of the adsorption was performed based on pseudo first order, pseudo second order, and intraparticle diffusion equations. From the research, it is known that the optimum conditions for the Chromium(VI) adsorption occurs at pH 2. The adsorption capacity of salacca peel based activated carbons for the removal of hexavalent chromium was found to be 123 mg/g. And the best adsorption isotherm which can represent the adsorption equilibrium is Langmuir isotermal adsorption model. Moreover the data indicated that the adsorption kinetics follow the pseudo second order